Suverenizem kot dekonstrukcija suverenosti - Kokol, Matevž (Teorija in praksa, 2015)
Sovereignty is one of the central political concepts that is important for understanding other political concepts. Its meaning is neither stable nor static, but depends upon contexts, the socio-political circumstances of any given historical moment as well as in- and extra-discursive elements. The article seeks to show the historical change and adaptability of the concept of sovereignty and questions its claim to be absolute. It focuses on the relationship between the concept of the state and sovereignty. It refutes the transhistorical understanding of the concept and argues for a conceptual novelty called sovereignism.
Keywords: dekonstrukcija; Država; Globalizacija; Globalization; Sovereignty; state; State, The; Suverenost; teorija; theory; zgodovina političnih idej